Discharge of granular materials from hoppers with various exit geometries - (:unkn) unknown (American Society of Mechanical Engineers (ASME), 2007)
The discharge of glass beads from axisymmetric hoppers was experimentally investigated. Two types of hoppers were employed: one was of conical hoppers with different angles and the other was nozzle-shaped. The result showed that, for a conical hopper with a hopper angle greater than 45°, the hopper angle had little effect on the discharge coefficient. On the other hand, for a hopper angle less than 45°, the discharge coefficient rapidly increased with decreasing hopper angle. The present data agreed well with other experimental data available in the literature. The discharge coefficient of the nozzle-shaped hopper was measured to be as considerably high as that of a conical hopper with the hopper angle of 10°. Preliminary investigation on velocity profiles at hopper exits was conducted by examining the traces of particles in digital photographs. Visual observation on the degree of spread of the jets of particles coming out of hoppers with different hopper angles indicated that the velocity profile at the exit for a narrow hopper was more uniform than that for a wide hopper. Copyright © 2007 by ASME.